2000
DOI: 10.1046/j.1365-2036.2000.014s2014.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: effect of bile salt pool composition on hepatic and biliary functions

Abstract: Summary The enterohepatic recirculation of bile salts exerts important regulatory effects on many hepatic, biliary and intestinal functions; such regulation is likely to depend, to a large extent, on the physical–chemical property of hydrophobicity of the recirculating pool. The present review summarizes the main experimental evidence carried out by our research group over the past two decades, in the attempt to investigate systematically the relationships between structural properties and biological effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…However, TC levels appeared to be lower in the previously mentioned studies (6.6-13% vs 13-66% in this study), while the percentage of C was higher (8.8-52% vs 0.14-1.46% in this study). CDC and DOC contents were also lower in this study, as compared with previous reports (Rossi et al 1987;Janowitz et al 1990) of gallstone patients who are well known to display a more lipophilic bile acid pool (Carulli et al 2000). In contrast to a previously reported study in which GC was found to be the most abundant bile salt in fasted state HIF (Persson et al 2005), TC was observed to be the major bile salt present in fasted state HIF in this study.…”
Section: Individual Bile Saltscontrasting
confidence: 65%
See 1 more Smart Citation
“…However, TC levels appeared to be lower in the previously mentioned studies (6.6-13% vs 13-66% in this study), while the percentage of C was higher (8.8-52% vs 0.14-1.46% in this study). CDC and DOC contents were also lower in this study, as compared with previous reports (Rossi et al 1987;Janowitz et al 1990) of gallstone patients who are well known to display a more lipophilic bile acid pool (Carulli et al 2000). In contrast to a previously reported study in which GC was found to be the most abundant bile salt in fasted state HIF (Persson et al 2005), TC was observed to be the major bile salt present in fasted state HIF in this study.…”
Section: Individual Bile Saltscontrasting
confidence: 65%
“…The hydrophilic-hydrophobic balance of the bile acid pool influences biliary lipid secretion, cholesterol synthesis, gallbladder emptying rate, cytotoxicity and apoptosis effect, and also affects the capacity to solubilize lipids and lipophilic drugs (Carey 1984;Carulli et al 2000). Taking into account the hydrophobic index (HI) values for the eleven different bile acid species studied, the HI for the different volunteers ranged from 0.14 to 1.08 (Table 4).…”
Section: Individual Bile Saltsmentioning
confidence: 99%
“…In addition, a separate study concluded that bile acid levels increased as early as 24 h postirradiation and remained persistently high three days after exposure (7). Under physiological conditions, 90% of bile acids are reabsorbed by the gut by the highly efficient enterohepatic recirculation system (38), which may indicate that the radiation-induced bile acid increases in the colonic contents is due to the reduction of intestinal absorption caused by radiation. The decrease in the secondary bile acid, ketodeoxycholic acid, is further evidence for the shift in the microbial metabolism and lower rate of deconjugation of bile salts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…97 A fraction of the 7-deoxy bile acids are absorbed from the colon and returned to the liver where they are efficiently reconjugated with glycine or taurine. 98,99 This variation in bile acid 7α-rehydroxylation activity is reflected in biliary DCA concentration that varies from 0-10% of bile acids in rats, mice, guinea pigs, prairie dogs, and hamsters; 100-103 15-30% in dogs and humans; 104,105 and greater than 90% in rabbits. Hepatic bile acid 7α-rehydroxylation varies considerably between species, but is essentially absent in humans.…”
Section: Biotransformation Of Bile Acids During Enterohepatic Cyclingmentioning
confidence: 99%